2019
DOI: 10.1038/s41598-019-41535-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Chaotic Resonance using External Feedback Signals in Neural Systems

Abstract: Stochastic resonance is a phenomenon in which the signal response of a non-linear system is enhanced by appropriate external noise. Likewise, a similar phenomenon can be caused by deterministic chaos; this is called chaotic resonance. Devices that employ stochastic resonance have been proposed for the purpose of enhancing tactile sensitivity. However, no applications of chaotic resonance have been reported so far, even though chaotic resonance exhibits a higher sensitivity than stochastic resonance. This contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…We previously reported that these characteristics are maintained under RRO feedback signals in discrete chaotic systems [38], [44], [45]. Therefore, the characteristics of chaotic resonance observed in this study are congruent with the previous findings of [19], [38], [44], [45].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We previously reported that these characteristics are maintained under RRO feedback signals in discrete chaotic systems [38], [44], [45]. Therefore, the characteristics of chaotic resonance observed in this study are congruent with the previous findings of [19], [38], [44], [45].…”
Section: Discussionsupporting
confidence: 93%
“…It is known that, in discrete and continuous chaotic systems with CCI, the signal response in chaotic resonance is also maximized at around the attractor-merging bifurcation, and its response exhibits dependency on the input frequency [19]. We previously reported that these characteristics are maintained under RRO feedback signals in discrete chaotic systems [38], [44], [45]. Therefore, the characteristics of chaotic resonance observed in this study are congruent with the previous findings of [19], [38], [44], [45].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Particularly, the chaotic resonance induced by the RRO feedback method exhibits higher sensitivity than stochastic resonances induced by additive noise and are more adaptable to various types of attractor conditions (Nobukawa et al, 2019b ). Studies on chaotic resonance induced by the RRO feedback method have been applied to neural systems (Nobukawa and Shibata, 2019 ; Nobukawa et al, 2019b ). Therefore, in addition to stochastic resonance controlled by additive noise in neural systems (Enders et al, 2013 ; Kurita et al, 2013 , 2016 ; Seo et al, 2014 ), chaotic resonance controlled by RRO feedback is at the stage where biomedical applications can be considered.…”
Section: Introductionmentioning
confidence: 99%